Germany's international branch campuses: neoliberalising the Humboldtian university through the backdoor? - Tim Rottleb; Marc Philipp Schulze; Jana Maria Kleibert (Compare: A Journal of Comparative and International Education, 2024)
While comprehensive research exists on transnational strategies of universities from the Anglosphere, little is known about why institutions from less marketised higher education systems engage in transnational education provision abroad. Based on semistructured interviews with decision-makers, we investigate why German public universities have established international branch campuses, and explore the underlying rationales and the consequences for university governance. We contribute to interdisciplinary transnational higher education literature by conceptualising the wider socio-political implications and spatialities of arguably nonmarket-driven transnational education. By analysing German branch campus projects against the backdrop of Anglosphere branch development, we show that although neoliberalisation has been subtle in German higher education, decision-making processes in university leadership are nonetheless strongly pervaded by a neoliberal paradigm. We argue that German branch campuses both reflect the specific form of German higher education's neoliberalisation and further accelerate their parent institutions' neoliberal reconfigurations by exposing them to commercialised higher education landscapes abroad.
Keywords: 300